A bibliometric analysis of the global research on biosimilars - Akram Hernández-Vásquez; Christoper A. Alarcon-Ruiz; Guido Bendezu-Quispe; Daniel Comandé; Diego Rosselli (Journal of Pharmaceutical Policy and Practice, 2018)
Background Biosimilars could be a promising option to help decrease healthcare costs and expand access to treatment. There is no previous evidence of a global bibliometric analysis on biosimilars. Therefore, we aimed to assess the quantity and quality of worldwide biosimilars research. Methods We performed a bibliometric analysis using documents about biosimilars published until December 2016 in journals indexed in Scopus. We extracted the annual research, languages, countries, journals, authors, institutions, citation frequency, and the metrics of journals. The data were quantitatively and qualitatively analyzed using Microsoft Excel 2013. Additional information about authors’ participation was obtained using the R-package Bibliometrix. Publication activity was adjusted for the countries by population size. Also, author co-citation analysis and a term co-occurrence analysis with the terms included in the title and abstract of publications was presented as network visualization maps using VOSviewer. Results A total of 2330 biosimilar-related documents identified in the Scopus database, most of them were articles (1452; 62.32%). The number of documents published had an exponential increased between 2004 and 2016 (p < 0.001). The United States was the country with the highest production with 685 (29.40%) documents followed by Germany and UK with 293 (12.58%) and 248 (10.64%), respectively. Switzerland (11.05), Netherlands (5.85) and UK (3.83) showed the highest per capita ratio. The highest citation/article ratio were for the Netherlands (28.06), Spain (24.23), and France (20.11). Gabi Journal published 73 (3.13%) documents; both Biopharm International and Pharmaceutical Technology and Mabs, 41 (1.76%). Three out of top ten journals were Trade publications. Amgen Incorporated from the USA was the most prolific institution with 51 documents followed by Pfizer Inc. with 48. Terms about specific diseases and drugs were found in recent years, compared with terms such as legislation, structure, protein, dose and generic in the early years. Conclusions Research production and publication of documents on biosimilars are increasing. The majority of publications came from high-income countries. The trends in terminology use are according to state of the art in the topic, and reflects the interest in the utilization of biosimilars in diseases who are expected to obtain benefits of its use.